Augmented reality fluoroscopy simulation of the guide-wire insertion in DHS surgery: A proof of concept study. (May 2018) - van Duren, B.H.; Sugand, K.; Wescott, R.; Carrington, R.; Hart, A.
Highlights: A fluoroscopic simulation system to augment DHS/CHS workshop bone simulation is described. The accuracy of the system's tip-apex measurement was tested in an experimental setup. Tests showed an average root mean square error of 4.2 mm. Augmented reality allows trainees to interact with real instrumentation. Abstract: Background: Hip fractures contribute to a significant clinical burden globally with over 1.6 million cases per annum and up to 30% mortality rate within the first year. Insertion of a dynamic hip screw (DHS) is a frequently performed procedure to treat extracapsular neck of femur fractures. Poorly performed DHS fixation of extracapsular neck of femur fractures can result in poor mobilisation, chronic pain, and increased cut-out rate requiring revision surgery. A realistic, affordable, and portable fluoroscopic simulation system can improve performance metrics in trainees, including the tip-apex distance (the only clinically validated outcome), and improve outcomes. Method: We developed a digital fluoroscopic imaging simulator using orthogonal cameras to track coloured markers attached to the guide-wire which created a virtual overlay on fluoroscopic images of the hip. To test the accuracy with which the augmented reality system could track a guide-wire, a standard workshop femur was used to calibrate the system with a positional marker fixed to indicate the apex; this allowed for comparison between guide-wire tip-apex distance (TAD) calculated by the system to be compared to that physically measured. Tests were undertaken to determine: (1) how well the apex could be targeted; (2) the accuracy of the calculated TAD. (3) The number of iterations through the algorithm giving the optimal accuracy–time relationship. Results: The calculated TAD was found to have an average root mean square error of 4.2 mm. The accuracy of the algorithm was shown to increase with the number of iterations up to 20 beyond which the error asymptotically converged to an error of 2 mm. Conclusion: This work demonstrates a novel augmented reality simulation of guide-wire insertion in DHS surgery. To our knowledge this has not been previously achieved. In contrast to virtual reality, augmented reality is able to simulate fluoroscopy while allowing the trainee to interact with real instrumentation and performing the procedure on workshop bone models.